2011
DOI: 10.1038/ejhg.2011.167
|View full text |Cite
|
Sign up to set email alerts
|

Detection of classical 17p11.2 deletions, an atypical deletion and RAI1 alterations in patients with features suggestive of Smith–Magenis syndrome

Abstract: Smith-Magenis syndrome (SMS) is a complex disorder whose clinical features include mild to severe intellectual disability with speech delay, growth failure, brachycephaly, flat midface, short broad hands, and behavioral problems. SMS is typically caused by a large deletion on 17p11.2 that encompasses multiple genes including the retinoic acid induced 1, RAI1, gene or a mutation in the RAI1 gene. Here we have evaluated 30 patients with suspected SMS and identified SMS-associated classical 17p11.2 deletions in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…High-density 17p11.2 aCGH and Sanger sequencing of RAI1 showed that 134 out of 149 individuals presented a genetic or genomic alteration of the RAI1 gene [9, 11, 17, 49–52], 96/134 (72 %) individuals carried the classic recurrent 3.7 Mb SMS deletion, ten (7.5 %) contained an uncommon recurrent 1 (UR1) or UR2 rearrangement, 24 (18 %) a non-recurrent RAI1 deletion, and four (3 %) had a de novo variant in RAI1 [9, 11, 49, 52, 53] (Additional file 2 Table S1). Whereas these proportions are similar to published results [12, 54], it is likely that some clinicians did not refer individuals with SMS features who were negative for SMS molecular diagnosis (via aCGH or fluorescence in situ hybridization, FISH) or who were positive for another potentially causative CNV, for example 1p36 deletion syndrome [15, 55, 56] that shares multiple similarities with SMS. Indeed, many individuals were molecularly diagnosed prior to sample submission.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…High-density 17p11.2 aCGH and Sanger sequencing of RAI1 showed that 134 out of 149 individuals presented a genetic or genomic alteration of the RAI1 gene [9, 11, 17, 49–52], 96/134 (72 %) individuals carried the classic recurrent 3.7 Mb SMS deletion, ten (7.5 %) contained an uncommon recurrent 1 (UR1) or UR2 rearrangement, 24 (18 %) a non-recurrent RAI1 deletion, and four (3 %) had a de novo variant in RAI1 [9, 11, 49, 52, 53] (Additional file 2 Table S1). Whereas these proportions are similar to published results [12, 54], it is likely that some clinicians did not refer individuals with SMS features who were negative for SMS molecular diagnosis (via aCGH or fluorescence in situ hybridization, FISH) or who were positive for another potentially causative CNV, for example 1p36 deletion syndrome [15, 55, 56] that shares multiple similarities with SMS. Indeed, many individuals were molecularly diagnosed prior to sample submission.…”
Section: Resultssupporting
confidence: 82%
“…Indeed, many individuals were molecularly diagnosed prior to sample submission. Consistent with this hypothesis, a separate study identified mutations affecting RAI1 in only 30 % of participants with a suspected diagnosis of SMS [12]. …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…A deletion of chromosome 17p11.2 was identified as the cause of this condition in approximately 90% of cases, and thus this disorder belongs to the group of contiguous-gene syndromes, currently referred to as genome diseases [3][4][5]. SMS patients without deletions 17p11.2 may carry a point mutation in the gene RAI1 [6][7][8][9][10], which codes a transcription factor acting in several different biological pathways. RAI1 dosage is crucial for normal regulation of circadian rhythm, lipid metabolism, and melatonin function.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, point mutations in the RAI1 (retinoic acid induced 1) gene have been identified in less than 10% of SMS patients [Slager et al, 2003;Bi et al, 2004Bi et al, , 2006Girirajan et al, 2005Girirajan et al, , 2006Vilboux et al, 2011;Vieira et al, 2012]. This gene maps in the SMS critical region [Bi et al, 2002;Vlangos et al, 2003].…”
mentioning
confidence: 99%